Does Corporate Governance or Corporate Performance Affect CSR Disclosure? - Susi Handayani; Eva Dwi Astutik (Universitas Pendidikan Indonesia, 2024)
This study aims to determine the relationship between Corporate Governance (CG), Company Performance (CP), and Corporate Social Responsibility (CSR) Disclosure. This research uses quantitative methods with secondary data sources. The data analysis technique tests the hypothesis using multiple linear regression with the help of SPSS software. This research indicates that corporate performance have positive impact on the CSR disclosure. The board of commissioners in Indonesian companies does not have the authority to pressure companies to care more about the environment and social communities. In addition, companies in Indonesia still adhere to a patrilineal kinship system so that men are in control, including in decision-making. This study suggest that companies can change the mindset of the patrilineal system in the hope that corporate governance can improve CSR disclosure. Beside that, the company can increase the number of independent commissioners in order have the authority to pressure companies to be more concerned about the environment and social communities. This research successfully proves that the patrilineal system is still in use in Indonesia. In addition, the company will disclose CSR activities when it has a good performance.